Housing Policy in Developing Countries : Conjectures and Refutations - Buckley, Robert M. (Oxford University Press on behalf of the World Bank, 2013)
This housing policy in developing countries, conjectures and refutations article discusses housing policy in developing economies. It examines recent research findings in light of earlier arguments as to the benefits of more market-oriented approaches. It also looks at whether the recommendations of earlier work have been refuted or developed in subsequent analyses and policy measures. In particular, it reviews the empirical analysis of the effects of policy on housing supply, the richer understanding of the effects that land market regulations have on housing affordability and the functioning of urban areas, and the alleged mysterious effects that researchers claim effective property rights have on housing policy and on development more generally. It also examines the effects of the increased emphasis on community participation, showing how it helps to more fully reconcile the incentives faced by beneficiaries of housing policy and donors. Finally, it examines recent literature on the welfare effects of rent control. The article shows that some of the conjectures as to the likely benefits of more market-based policy have been refuted, but large welfare gains for poor people can still be realized by adapting this approach. Furthermore, this approach appears to be gaining ground as the consensus approach to effective housing policy.